2018
DOI: 10.1016/j.bbrep.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Serum circulating cell free DNA as potential diagnostic and prognostic biomarker in non small cell lung cancer

Abstract: BackgroundNon-small cell lung cancer (NSCLC) is leading cause of cancer related death and the survival rate for patients with NSCLC remain poor so early diagnosis of NSCLC represents the best opportunity for cure. Cell-free DNA (cf-DNA) is extracellular nucleic acids found in cell-free plasma/serum of humans, given the recent approval of a liquid biopsy in lung cancer, the use of circulating tumor DNA as a novel non-invasive diagnostic and prognostic biomarker is promising.ObjectivesStudying whether the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…Even though we observed a significant difference in the plasma concentration of ALU115 and ALU247 between benign and malignant thyroid nodules, its clinical utility is limited due to a significant overlap. Although various studies have reported an increase in DNA concentration in cancer patients (22)(23)(24)(25)(26), numerous studies have indicated the limited utility of cfDNA concentration as a biomarker, owing to the wide variations in cfDNA level among the population (11). Moreover, we observed that the concentration difference could be attributed to the size of the lesions since patients with benign lesions were characterized by the larger tumor size, which was associated with the higher ALU115 and ALU247 levels.…”
Section: Discussionmentioning
confidence: 63%
“…Even though we observed a significant difference in the plasma concentration of ALU115 and ALU247 between benign and malignant thyroid nodules, its clinical utility is limited due to a significant overlap. Although various studies have reported an increase in DNA concentration in cancer patients (22)(23)(24)(25)(26), numerous studies have indicated the limited utility of cfDNA concentration as a biomarker, owing to the wide variations in cfDNA level among the population (11). Moreover, we observed that the concentration difference could be attributed to the size of the lesions since patients with benign lesions were characterized by the larger tumor size, which was associated with the higher ALU115 and ALU247 levels.…”
Section: Discussionmentioning
confidence: 63%
“…The concentration of tumor-associated biomarkers released into the bloodstream might contribute to early detection of cancer and more favorable prediction of patients’ prognosis [ 84 ]. The emerging role of blood-based liquid biopsy in the management of cancer patients [ 85 ] in terms of predictive, personalized, and preventive medicine is based on the analysis of CTCs, genetic and epigenetic changes at the ctDNA level (such as mutations or DNA methylation) [ 86 , 87 , 88 , 89 , 90 ], EVs and their content derived from the original cancer cell [ 91 , 92 , 93 ], and protein-based markers [ 94 , 95 , 96 , 97 ] or their combinations [ 98 ] ( Figure 2 ). Therefore, the detection of tumor biomarkers freely circulating in blood through liquid biopsy is associated with new opportunities for early diagnosis and therapy of cancer [ 99 , 100 ].…”
Section: Blood Samples As Currently Most Frequently Used Liquid Bimentioning
confidence: 99%
“…Circulating tumor cell-free DNA (ctDNA) is defined as tumor-derived extracellular nucleic acid in cell-free plasma or serum that is currently gaining a promising potential as a novel diagnostic and prognostic tool in cancer management [ 86 , 93 , 101 ]. Peripheral blood is the most common source of ctDNA but it could be detected also in other biofluids such as saliva, urine, ascites, and PE [ 102 ].…”
Section: Blood Samples As Currently Most Frequently Used Liquid Bimentioning
confidence: 99%
See 2 more Smart Citations